Peer firms' credit rating changes and corporate financing. Issue 1 (2nd January 2020) - Hung, Chi-Hsiou D.; Naeem, Shammyla; John Wei, K.C.
Abstract : We find that firms reduce net debt issuance ( NDI, hereafter) when industry peers with the same credit rating were downgraded in the previous year, as opposed to an average NDI increase among all firms. This finding is consistent with the considerations of competition and contagion associated with relative strengths and weaknesses in credit quality. The peer effect on NDI reduction is ubiquitous across both speculative- and investment-grade firms, but is particularly strong for small size firms with speculative-grade ratings, and firms operating in concentrated industries, and in times when the economy is in expansion or outside financial crises. We also find that firms reduce leverage when their ratings are lower than the industry average, and that peer firms' rating effects remain strong even when controlling for the lower-than-average effect.